Problematika Kelembagaan Satuan Tugas PPKPT dalam Penanganan Kekerasan di Perguruan Tinggi - Wiwin Wiwin (Jurnal Litigasi Amsir, 2026)
Violence in higher education constitutes a critical issue that requires an institutional mechanism capable of providing protection for victims while ensuring an objective and accountable handling process. The establishment of the Task Force for the Prevention and Handling of Violence in Higher Education (Satgas PPKPT) through Minister of Education, Culture, Research, and Technology Regulation No. 55 of 2024 represents an effort to develop a dedicated institutional mechanism for preventing and addressing violence within higher education institutions. However, the institutional design of the Task Force, which is integrated within the university structure and endowed with investigative authority and the power to issue recommendations, raises concerns regarding independence, division of authority, and the guarantee of due process of law. This study aims to analyze the institutional construction of the Satgas PPKPT and to identify its institutional challenges in handling violence in higher education. It employs a normative-empirical legal research design using statutory, conceptual, and case approaches, with legal materials and data analyzed qualitatively through a comparison between the normative institutional framework of the Task Force and its practical implementation in handling cases of violence. The findings indicate that Ministerial Regulation No. 55 of 2024 has established a comprehensive institutional framework for the Task Force, including provisions on its position, composition, duties, functions, authority, investigative procedures, recommendations, and objection mechanisms; however, several issues persist, particularly concerning the relationship between the Task Force’s position within the internal university structure and the requirement for functional independence, the delineation of authority between the Task Force and university leadership in determining case outcomes, and the assurance of due process of law for both victims and respondents. These challenges reflect a tension between institutional design, independence, distribution of authority, and procedural justice, which may affect the overall quality of violence handling in higher education institutions.